PROJECT SUCCESS AND INDIVIDUAL ENTREPRENEURIAL ORIENTATION OF PROJECT MANAGERS: RUSSIAN CONTEXT - C. A. Titov; R. D. Pathak; A. A. Tsymbal (Стратегические решения и риск-менеджмент)
Projects implemented in conditions of high uncertainty are sometimes called entrepreneurial projects. Success in such projects is more difficult to achieve. To successfully manage entrepreneurial projects, project managers should have entrepreneurial skills. The article explores two issues related to project success, entrepreneurial characteristics, and project uncertainty. First, the article tries to find out whether the increase in the entrepreneurial nature of the project, manifested in the increase in project goals and methods uncertainty, is accompanied by a decrease in project success. Second question is – does the entrepreneurial orientation of project managers affect project success and the relationship between the projects’ success and their entrepreneurial features. To answer these questions, data were collected from Russian project managers assessing the entrepreneurial nature of projects, project success and the individual entrepreneurial orientation of project-managers. The collected data were examined using factor and regression analysis. The findings indicate that there is a negative relationship between the entrepreneurial nature and such indicators of project success as internal efficiency, preparation for the future, and results for clients. Some indicators of success were positively associated with such indicators of entrepreneurial orientation as proactivity and risk taking. As uncertainty increased, some measures of individual entrepreneurial orientation of project managers can positively compensate negative impact on project success from uncertainty associated with projects’ entrepreneurial nature.